Revision of Australian species of the dung beetle genus Lepanus (Coleoptera: Scarabaeidae: Scarabaeinae): review of the L. ustulatus, L. storeyi, and L. nitidus species groups and description of eight new species - Gunter, Nicole L.; Weir, Thomas A. (Zootaxa, 2021)
This publication is the third part of an ongoing revision of Australian species of the genus Lepanus (Coleoptera: Scarabaeidae: Scarabaeinae) and revises three species groups. Keys to species within the L. ustulatus, L. storeyi, and L. nitidus species groups are provided and eight new species are described. Within the L. ustulatus species group, L. ustulatus (Lansberge, 1874) and L. globulus (Macleay, 1887) are redescribed and three new species are described: Lepanus cameroni new species from Cape York Peninsula, far north Queensland; Lepanus cardwellensis new species from the Australian Wet Tropics, northern Queensland; and Lepanus lemannae new species from the Australian Wet Tropics to the Central Mackay Coast, Queensland. Within the L. storeyi species group, L. storeyi Weir & Monteith, 2010 is redescribed and two new species are described: Lepanus meierae new species from southeastern Queensland to Wollongong, New South Wales and Lepanus williamsi new species from eastern New South Wales. Within the L. nitidus species group, L. nitidus Matthews 1974 and L. dichrous Gillet, 1925 are redescribed and three new species are described: Lepanus vangerweni new species, Lepanus carbinensis new species, and Lepanus kulki new species from the Australian Wet Tropics, northern Queensland. Following these descriptions, a total of 50 Lepanus species are now described from Australia.